Prevalencia de fluorosis y caries dental en la zona urbana del municipio de Yondó - Rosa Virginia López-Camacho; Hernando Molina-Saldarriaga (Revista Facultad de Odontología Universidad de Antioquia, 1997)
Due to its high prevalence and incidence, dental caries has been a Public Health problem of considerable proportions in the world. According to data obtained in the National Study on Health 1977/1980, 967% of the Colombian population suffers or has been affected by this dental pathology. Due to the great magnitud of the problem fluoride has been used because it is an effective anticariogenic agent given by local or systemic means. The confidence in the innocuousness and efficiency of Euoruration hashed as a result the incoming of dentalfluorosisin some individuals and populations due to the accumulative effect that occurs at a systemic level. In this investigation, 375 residents of the urban zone of the municipality of Yondo (Antioquia) were interviewed and examined in order to measure. The magnitude of fluorosis and dental caries, using for such end the indexes of Dean, C.O.P.-D. and c.e.o.-d. This population consumes water with a content of natural fluoride of 2.1 p.p.m. (1 pp.m. equals to 1 mg-. of fluoride in 1 liter of water), 3 times above the optimum which according to the Public Health Service of USA. should be 0.6-0.8 p.p.m. in order to guarantee the control of dental caries without the risk offiuorosis. Besides this risk factor, kitchen salt with irregular quantities of the ion is distributed, and there is a supply of fluoride for local use (mouthrinses and dentrifices). In the population of 5 and more age a prevalence of 87% of dentallluorosis was determined, being the moderate degree the most frecuent The prevalence of denial caries was 77.3%. The results obtained contribute to the knowledge on the effects of fluoride in oral health and guide their use in the preventive programs on dental caries, especially in Colombian communities where the water for consumption contains high concentrations of this ion.